SEJARAH KAMPUNG PONDOL DAN KOMUNITAS EKSIL MUSLIM DI KOTA MANADO - Roger Allan Christian Kembuan (Aqlam: Journal of Islam and Plurality, 2020)
Abstract: This research discusses the process of forming and developing of Pondol village in Manado as a location for exile along with the Dutch colonial government policy that placed exiles who came from several sultanates in Java in the Manado Residency during the 19th century. The discussion includes, first, the background of the exile of the Javanese aristocrats in Manado. Second, the process of establishing Pondol as a location for exile and its development during the XIX century, and third, the adaptations made by the exiles to adjust to their exile and the impact of their arrival on the Manado-Minahasa community. The historical method is used in this research, using colonial archives from the XIX century which are stored in the National Archives of the Republic of Indonesia, and local sources, especially manuscripts stored by their descendants in Manado and Java. The findings in this study are; Kampung Pondol was formed due to the isolation of Kanjeng Ratu Sekar Kedaton and Pangeran Suryeng Ingalaga and some of his followers originated from political intrigue that occurred in the Sultanate of Yogyakarta. Second, the reason why Kampung Pondol was chosen as the new location for exile by the Dutch colonial government for Javanese royal officials was different from the exile of other figures in Tondano and Tomohon. Third, the form of adaptation carried out by the exiles in Kampung Pondol Manado was marriage with women from Manado and relationships with Dutch people who lived around them.Keywords : Exile, Javanese Noble, Pondol Village, Adaptation. Abstrak: Penelitian ini membahas tentang proses terbentuk dan perkembangan kampung Pondol di Manado sebagai lokasi pengasingan seiring dengan kebijakan pemerintah kolonial Belanda yang menempatkan para eksil yang berasal dari beberapa kesultanan di Jawa di Karesidenan Manado pada sepanjang abad 19.  Pembahasannya meliputi; Pertama, Latar belakang pengasingan para bangsawan Jawa di Manado. Kedua, proses terbentuknya Pondol sebagai lokasi pengasingan dan perkembangannya selama abad XIX, dan Ketiga, adaptasi yang dilakukan para eksil untuk menyesuaikan diri di pengasingan serta dampak kedatangan mereka pada masyarakat Manado-Minahasa. Metode sejarah dipergunakan dalam penelitian ini, dengan mempergunakan sumber Arsip Kolonial kurun waktu abad ke XIX yang tersimpan di Arsip Nasional Republik Indonesia,  dan sumber lokal terutama manuskrip yang tersimpan oleh keturunannya di Manado dan Jawa. Temuan dalam penelitian ini adalah; Kampung Pondol terbentuk karena Pengasingan Kanjeng Ratu Sekar Kedaton dan Pangeran Suryeng ingalaga dan beberapa pengikutnya berawal dari intrik politik yang terjadi di Kesultanan Yogyakarta. Kedua, alasan Kampung Pondol dipilih sebagai lokasi baru pengasingan Pemerintah Kolonial Belanda bagi pembesar kerajaan Jawa yang berbeda lokasi dengan pengasingan tokoh-tokoh lainnya di Tondano dan Tomohon. Ketiga, bentuk adaptasi yang dilakukan oleh para eksil di Kampung Pondol Manado dilakukan pernikahan dengan wanita dari Manado dan relasi dengan orang-orang Belanda yang tinggal disekeliling mereka.Kata Kunci : Eksil, Bangsawan Jawa, Kampung Pondol, Adaptasi.